Adubação nitrogenada e potássica na produção e qualidade de goiabas no Distrito Irrigado do Baixo Açu (RN) - Alencar, Renato Dantas (2011)
It was evaluated the effect of nitrogen and potassium fertilization on the yield and quality of Paluma guava fruits grown in a commercial orchard located in the Irrigated Baixo Açu District. It was carried out two experiments: one with increasing nitrogen doses and the other with increasing potassium doses. In both experiments it was utilized a split-plot scheme in a randomized blocks design, with five treatments and four replications. To the split plots were assigned the harvest seasons (two). For evaluations it was utilized only the three center plants of each subplot. In the experiment 1 the treatments were the nitrogen doses (0, 0.4, 0.8, 1.2 and 1.6 kg plant-1) and in the experiment 2, the potassium doses (0, 0.5, 1.0, 1.5 and 2.0 kg plant-1). As sources of nitrogen and potassium it was utilized urea and potassium chloride, respectively. The fruits were evaluated quantitatively (number per plant, mean weight, total weight, and yield) and qualitatively (pulp firmness, longitudinal and transverse diameters, potential of hydrogen (pH), soluble solids content (SS), vitamin C, and titratable acidity). Nitrogen fertilization did not cause significant effect on fruit quality, but the greatest yield was obtained at the estimated dose of 0.4 kg N plant-1, with the higher doses causing yield reduction. The effect of the potassium fertilization on the number of fruits per plant was increasingly linear in function of the increasing doses of K2O, but the greatest yield and pulp firmness were obtained, respectively, at the estimated doses of 0.37 and 1.21 kg K2O plant-1